48 Variations in endometrial cancer risk and histologic distribution by caribbean nativity. (18th September 2019) - Schlumbrecht, M; George, S; Pinto, A; Huang, M; Slomovitz, B; Koru-Sengul, T
Abstract : Objectives: Prior data suggest that within subpopulations of racial and ethnic minorities, endometrial cancer (EC) risk varies. Nativity as mediator of risk has been poorly studied. Our objective was to determine if Caribbean nativity influences EC risk and presentation. Methods: Using the Florida Cancer Data System (FCDS), we identified women diagnosed with EC from 1981–2013. Demographics and pathologic factors were abstracted. Caribbean nativity included countries of both African and Hispanic lineage. Statistical analyses were performed using logistic regression and chi-square, with statistical significance at p<0.05. Results: Of the 23, 690 women in the FCDS identified with EC, 840 had Caribbean nativity. Among Caribbean immigrants with EC, a higher proportion had type II histologies compared to US natives (35.6% vs. 27.5%, p<0.01), with very high prevalence seen among Haitian (54.2%, p<0.01) and Jamaican (47.1%, p<0.01) women. In comparison to US-born women, uterine serous carcinoma was more prevalent in women from Guyana (22.2% vs. 6.5%, p=0.03) and Jamaica (13.8% vs. 6.5%, p=0.001), with carcinosarcoma more prevalent in women from Haiti (13.5% vs. 4.6%, p<0.01) and Jamaica (13.8% vs. 4.6%, p<0.01). More Caribbean immigrants presented with distant disease (10.1% vs. 6.9%, p<0.01). Relative to US natives, significant increases in type II EC risk were seen in women born in Haiti (OR 3.08 [2.06–4.62], p<0.01) and Jamaica (OR 2.32 [1.66–3.25], p<0.01). Conclusions: Women of Jamaican and Haitian birthplace have increased risks of type II EC compared to US-born women. Caribbean natives also have a higher prevalence of type II histologies. Effect of nativity on EC warrants further study.